Confronting the Past. Trauma, History and Memory in Wajda’s film - Bondebjerg, Ib (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Confronting the Past. Trauma, History and Memory in Wajda’s film Historical films are important carriers of collective memory, and as a genre historical films can activate both strong feelings and strong debate. Historical fiction films often tell very accurate and almost documentary stories, but fictional films have the freedom to make historical reality in quite another way than factual historical films. This article deals with some of the most important historical film genres and uses a general theory of genres, emotions, memory and history to analyse the historical films of Polish film director Andrzej Wajda, especially those made post 1989. Dealing with both his heritage drama Pan Tadeusz (1999) and critical historical drama Katyń (2007), the article analyses the ways in which Wajda uses historical narratives to comment on both history and contemporary society, and how this strategy is reflected in all his historical films. The article argues that the traumatic and contrast-filled history of Poland makes historical films especially important and interesting as a critical part of public debate and the reframing and reinterpretation of the past.